Avaliação das propriedades fotocatalíticas do ZnWO4 e Fe2WO6 na degradação do corante azul de metileno - Macêdo, Olívia Bezerra de (2021)
Zinc Tungstate (ZnWO4) and Iron Tungstate (Fe2WO6) were synthesized by the Pechini method. To optimize the synthesis of ZnWO4, precursors such as Zinc Acetate dihydrate Zn(NO3)2.6H2O and Zinc Nitrate hexahydrate (C4H6O4Zn.2H2O) were tested, in addition to calcination levels of 400°C/2 h followed by 700°C /4 h and direct plateau of 700°C/4 h, this last plateau, together with the precursor Zn(NO3)2.6H2O, which resulted in obtaining the pure phase of ZnWO4. For Fe2WO6, phase monitoring was carried out based on variations in calcination temperatures (400 - 800°C), and at 500°C the formation of the Fe2WO6 phase was observed, and at 800°C a greater crystallinity was obtained. Characterizations were carried out: X-Ray Diffraction, Infrared (IR) Spectroscopy and Raman Spectroscopy in order to prove the formation of ZnWO4 and Fe2WO6 by the Pechini method. From the Absorption Spectroscopy in the Ultraviolet Region - Visible (UV-vis) the band gap of ZnWO4 was determined as being 3.20 eV and Fe2WO6 as being 1.97 eV. Morphological analysis by scanning electron microscopy showed the formation of agglomerated particles for both tungstates. The zero charge point (PCZ) for ZnWO4 was at pH = 2.19 and for Fe2WO6 was at pH = 2.54. As pH values increase, both semiconductors have negative surfaces. The evaluation of photocatalytic activities of zinc and iron tungstates were carried out under UVC irradiation (λ= 254 nm) for terephthalic acid (AT) for quantification of hydroxyl radicals (•OH) from fluorescence spectroscopy. For the photocatalysis of methylene blue dye (MB), using concentrations of 0.5, 0.8 and 0.85 mg.mL-1 for the catalysts ZnWO4 and Fe2WO6, the effect of pH on the photocatalytic activity was verified, considering pH = 5, 7 and 11. It was found that Fe2WO6 had a lower photocatalytic efficiency reaching 55.71% in 8 h of reaction in the degradation of MB ZnWO4, on the other hand, showed an efficiency of 99.34% in 2h in dye degradation. The higher intensity in the production of •OH radicals and higher dye adsorption as a function of the material's surface charge were determining factors for ZnWO4 to achieve a better photocatalytic performance in the degradation of the MB cationic dye.